Risk of alterations in neurodevelopment in infants and preschool children with cancer - Liliana Velasco-Hidalgo; Alejandro González-Garay; Antonio Rizzoli-Córdoba; Roberto Rivera-Luna; Alda García-Guzmán; Ana G. Ortiz-Razo; Evereth A. Olmedo-Jiménez; Rocío Cárdenas-Cardos; Kenya S. Carmona-Jaimez; Marta M. Zapata-Tarrés (Permanyer, 2024)
Background: Some cancer survivors experience difficulties with concentration, attention, and memory; however, there are no studies on neurodevelopment in patients under 5 years of age who are undergoing cancer treatment. Our aim was to evaluate neurodevelopment in cancer patients under 5 years of age using the Early Development Instrument (EDI) test, considering factors such as nutritional status, type of cancer, and treatment effect. Methods: A cross-sectional study was conducted from February 2018 to March 2019. Patients with cancer diagnoses outside the central nervous system in any phase of cancer treatment were included. Results: A total of 45 patients were included. Regarding fine motor skills, 28% of patients with retinoblastoma and 23% of patients with leukemia or lymphoma had a risk of developmental delay compared to 0% of patients with solid tumors (p = 0.025). The final results showed that 19 (42.2%) patients had normal neurodevelopment (gray), 7 (15.5%) had a delay in neurodevelopment (light gray), and 19 (42.2%) had a risk of developmental delay (black). Regarding developmental delay, 52% of patients in the leukemia and lymphoma group, 71% in the retinoblastoma group, and 23% in the solid tumor group presented developmental delay (p = 0.06). Conclusions: The risk of delay and lag in neurodevelopment is common in cancer patients under 5 years of age undergoing treatment. However, more studies are required to evaluate the effect of treatment on this group of patients as it may be affected by various factors.